Knowledge, attitudes, and decision-making regarding hyperbaric oxygen-assisted cancer treatment among related healthcare professionals - Zhou, Cheng; Zhang, Jia; Dai, Zhengze; Fu, Dalin; Sun, Yi; Wu, Guopei; Chen, Linsheng; Lu, Xiao (Frontiers in Oncology, 2026)
AimsThis study aimed to evaluate the knowledge, attitudes, and clinical decision-making of healthcare professionals in hyperbaric oxygen therapy (HBOT) units and oncology specialties regarding HBOT as an adjunctive cancer treatment.MethodsA cross-sectional survey was conducted between February, 2024 and February, 2025. Data were collected using a structured questionnaire, which included sections on demographic characteristics and assessed participants’ knowledge, attitudes, and practices (KAP) related to hyperbaric oxygen-assisted cancer therapy. The KAP scores were calculated to quantify the respondents’ familiarity with and perspectives on the treatment.ResultsOf 202 valid questionnaires, 58.91% were physicians. The majority (63.86%) had over 15 years of clinical experience, and 79.70% reported prior HBOT training in oncology. The mean scores were 52.87 ± 12.21 for knowledge, 41.24 ± 5.92 for attitudes, and 22.40 ± 2.38 for decision-making. Analysis indicated that knowledge positively influenced attitudes (β=0.393, P = 0.013) and decision-making (β = 0.159, P = 0.018), while attitudes significantly impacted decision-making (β = 0.318, P = 0.012). Knowledge indirectly affected decision-making via attitude (β = 0.125, P = 0.004).ConclusionsHealthcare professionals working in HBOT units and oncology-related specialties demonstrated a generally adequate level of knowledge, positive attitudes, and a proactive approach toward the use of HBOT as an adjunctive cancer treatment, with attitude emerging as a key mediator linking knowledge to clinical decision-making. These findings highlight the importance of targeted educational interventions aimed at strengthening both knowledge and attitudes, which may in turn enhance evidence-based clinical decision-making and support the broader integration of HBOT into oncologic care pathways.